Clinical isolates of Providencia rettgeri and Providencia Stuartii evades neutrophil-mediated killing by subverting neutrophil-extracellular traps - Castro, Joselyn E.; Birnberg-Weiss, Federico; Toloza, María J.; Bertinat, Yasmín A.; Fuentes, Federico; Peyloubet, Agustín; Faccone, Diego; Gómez, Sonia A.; Landoni, Verónica I.; Fernández, Gabriela C. (Frontiers in Immunology, 2025)
IntroductionProvidencia rettgeri (Pr) and Providencia stuartii (Ps) are clinically relevant opportunistic pathogens. They are resistant to several antibiotics including carbapenems. The immune response against these pathogens has never been investigated. Here, we aimed to evaluate whether neutrophils (PMN), key players against bacterial infections, were able to recognize and eliminate these bacteria.MethodsWe measured PMN functions after challenge with selected clinical isolates of Pr and Ps, and used Escherichia coli ATCC (Eco), which fully activates PMN, for comparison. Bacterial survival was evaluated after exposure of PMN to bacteria for 1 or 3 h and colony formation units (CFU) were determined.ResultsWhile PMN were able to partially contain Ps growth at 1 h, at 3 h both Pr and Ps were able to escape PMN-mediated killing compared to Eco, which was efficiently killed. Reactive oxygen species (ROS) generation was not induced by Pr or poorly induced by Ps, compared to Eco, but phagocytosis of Pr, Ps, and Eco was similar. Although Pr and Ps induced the release of double-stranded (d.s.) DNA early at 30 min (vital neutrophils extracellular traps or NETs), the release of late-induced NETs (3 h, suicidal NETs) was not observed, consistent with the absence of PMN death observed with Pr or Ps. In addition, Pr and Ps decreased suicidal NETs when Eco or PMA were used as inducers. This decrease was abolished by fixed bacteria, and was dependent on the release of a DNase activity. Twenty-four h after i.p. inoculation of mice with Pr, Ps or Eco, all bacteria induced migration of PMN to the peritoneum, but no PMN activation or NETs was observed in Pr or Ps-treated mice. When the distribution of bacteria in different organs was measured by CFU determination, Pr and Ps disseminated to the spleen and lungs, whereas Eco was exclusively present in the peritoneum.DiscussionThe isolates used in this study of Pr and Ps are poor inducers of bactericidal PMN responses and display immune evasion strategies to subvert PMN-mediated killing. These evasion mechanisms, acting on degrading vital NETs and/or blocking the formation of suicidal NETs, would favor bacterial dissemination.